1999
DOI: 10.1152/ajpgi.1999.277.5.g993
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tachyarrhythmias during small bowel ischemia

Abstract: The electrical control activity (ECA) of the bowel is the omnipresent slow electrical wave of the intestinal tract. Characterization of small bowel electrical activity during ischemia may be used as a measure of intestinal viability. With the use of an animal model of mesenteric ischemia, serosal electrodes and a digital recording apparatus utilizing autoregressive spectral analysis were used to monitor the ECA of 20 New Zealand White rabbits during various lengths of ischemia. ECA frequency fell from 18.2 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Sarna and Otterson (23) described the occurrence of what they labeled amyogenesia (abolition of slow waves) and dysmogenesia (irregular slow waves) in dogs upon infusion by morphine or loperamide and related them to cardiac and skeletal muscle fibrillation. Intestinal ischemia in the rabbit has been shown to induce tachyarrhythmia (27) and, in an inflammation-induced motor dysfunction in the mouse small intestine, a patchwork of electrical quiescence occurring next to areas with normal or high-frequency slow wave activity were noted (5). Most recently, a tachyduodenia was detected in a patient suffering from a mitochondrial encephalomyopathy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Sarna and Otterson (23) described the occurrence of what they labeled amyogenesia (abolition of slow waves) and dysmogenesia (irregular slow waves) in dogs upon infusion by morphine or loperamide and related them to cardiac and skeletal muscle fibrillation. Intestinal ischemia in the rabbit has been shown to induce tachyarrhythmia (27) and, in an inflammation-induced motor dysfunction in the mouse small intestine, a patchwork of electrical quiescence occurring next to areas with normal or high-frequency slow wave activity were noted (5). Most recently, a tachyduodenia was detected in a patient suffering from a mitochondrial encephalomyopathy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies ranged from 25 to 50 cpm. These tachyarrhythmias were seen only during ischemia, suggesting that they are pathognomonic for intestinal ischemia [44]. In patients with intestinal idiopathic pseudo-obstruction, responses of intestinal myoelectrical activity to distention was found to be altered [45].…”
Section: Intestinal Slow-wave Dysrhythmiamentioning
confidence: 95%
“…However, a number of studies did report intestinal slowwave dysrhythmia in a number of clinical settings such as nausea and vomiting, intestinal pseudo-obstruction and intestinal ischemia [45,[55][56][57][58][59]. Abnormalities in intestinal slow waves include dysrhythmia, reduced frequency, and uncoordinated slow waves along the intestine, and are associated with impaired intestinal contractions [42,44].…”
Section: Effects On Intestinal Slow-wave Dysrhythmiamentioning
confidence: 99%
“…Serum assays such as D-dimers [112][113][114] , alcohol dehydrogenase [115] , glutathione S-transferase [116] and cobalt-albumin binding [117] , and measurement of pH and potassium in peritoneal irrigation fluid [118] , as well as liver tissue oxygenation index [119] are good examples of current research. Seidel et al showed that mesenteric electrical activity may detect mesenteric ischemia with a high degree of sensitivity and specificity [120] . However, promising studies in animals remain to be validated under clinical conditions.…”
Section: Perspectives For the Futurementioning
confidence: 99%